Analisis Faktor Keaktifan Kader Posyandu di Wilayah Kerja UPTD Puskesmas Simpang Kiri Subulussalam - Nelizar, Nelizar; Raisah, Putri; Putri, Rosalia (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT Posyandu activities consist of main activities and development/elective activities. Posyandu is the government's effort to make it easier for the Indonesian people to obtain maternal and child health services. Health services in Posyandu are very dependent on HR (Human Resources) in the organization, especially Posyandu cadres. To find out the analysis of cadre activity in the UPTD work area, Simpang Kiri Health Center, Subulussalam Regency in 2023. Quantitative research with analytical descriptive design or cross-sectional approach. The population in this study is all Posyandu cadres in the UPTD Simpang Kiri Health Center work area as many as 52 people. Sampling using probability techniques is a saturated sample or often called total population. The data analysis carried out is chi-square analysis. The results of the univariate analysis showed that 55.8% of cadres were less active (55.8%), cadres had good knowledge (69.2%), cadres had high motivation (55.8%), cadre family support (67.3%), cadres were good at communicating health workers (63.5%), and 50% support community leaders supported. The results of the bivariate analysis static test can be concluded that there is a relationship between knowledge (p-value = 0.007), motivation (p-value = 0.009), health worker communication (p-value = 0.004), community leader support (p-value = 0.005), and there is no relationship between family support (p-value = 0.229) and the activeness of Posyandu cadres. There is a relationship between knowledge, work, motivation, family support, communication with health workers, support from community leaders and the activity of posyandu cadres in the UPTD Simpang Kiri Health Center work area of Subulussalam Regency in 2023. Keywords: Knowledge, Motivation, Family Support, Cadre Activity.  ABSTRAK Kegiatan Posyandu terdiri dari kegiatan utama dan kegiatan pengembangan/pilihan. Posyandu merupakan upaya pemerintah untuk memudahkan masyarakat indonesia dalam memperoleh pelayanan kesehatan ibu dan anak. Pelayanan kesehatan di Posyandu sangat tergantung pada SDM (Sumber Daya Manusia) dalam organisasi terutama kader Posyandu. Untuk mengetahui analisis keaktifan kader di  wilayah kerja UPTD Puskesmas Simpang Kiri Kabupaten Subulussalam Tahun 2023. Penelitian kuantitatif dengan rancangan deskriptif analitik atau pendekatan cross-sectional. Populasi dalam penelitian ini ialah seluruh kader Posyandu di wilayah kerja UPTD Puskesmas Simpang Kiri Kabupaten Subulussalam sebanyak 52 orang. Pengambilan sampel menggunakan teknik probability yaitu sampel jenuh atau sering disebut total population. Analisa data yang dilakukan adalah analisa chi-square. Hasil penelitian analisis univariat menunjukkan bahwa 55,8% kader kurang aktif (55,8%), pengetahuan kader baik (69,2%), kader memiliki motivasi tinggi (55,8%), dukungan keluarga kader mendukung (67,3%), kader baik dalam berkomunikasi tenaga kesehatan (63,5%), dan 50% dukungan tokoh masyarakat mendukung. Hasil uji statiktik analisis bivariat dapat disimpulkan bahwa ada hubungan antara pengetahuan (p-value=0,007), motivasi (p-value=0,009), komunikasi tenaga kesehatan (p-value=0,004), dukungan tokoh masyarakat (p-value=0,005), dan tidak ada hubungan antara dukungan keluarga (p-value=0,229) dengan keaktifan kader Posyandu. Terdapat hubungan antara pengetahuan, pekerjaan, motivasi,  dukungan keluarga, komunikasi dengan tenaga kesehatan, dukungan tokoh masyarakat dengan keaktifan kader posyandu di wilayah kerja UPTD Puskesmas Simpang Kiri Kabupaten Subulussalam tahun 2023. Kata Kunci: Pengetahuan, Motivasi, Dukungan Keluarga,  Keaktifan Kader.